On the Influence of Catalyst Mesopore Structure in the Catalytic Cracking of Polypropylene - Rejman, Sebastian; Meijer, Tim; Seyed Khabbaz, Hamid; Gooneie, Ali; Duijndam, Adriaan J. A.; van de Minkelis, Johan H.; Vollmer, Ina; Weckhuysen, Bert M. (ChemistryEurope, 2025)
Catalytic cracking, one of the core processes of the refining of crude oil, is gaining industrial adoption to convert hard‐to‐recycle polyolefin plastics back into hydrocarbon feedstocks. While structure–composition–performance relationships for converting shorter hydrocarbons over solid acid catalysts, including zeolite‐based materials, have been studied extensively, studies focusing on utilizing polyolefins are only now emerging. In this work, the effect of the catalyst pore size distribution in the catalytic cracking of polypropylene is isolated. This is achieved by preparing a set of amorphous silica–alumina (ASA) materials with close to identical external acidity (≈30 µmol g −1 ) from silica supports of pore diameters ranging from 7 to 75 nanometers and particle sizes ranging from 1 to 40 µm. Surprisingly, it is observed that the mesopore pore size has only a minor effect on cracking activity, as measured by ramped thermogravimetric analysis at high PP:catalyst ratio. The results are rationalized by conducting a simplified simulation of pore intrusion utilizing the Lucas–Washburn equation of capillary flow, which suggests that pore filling can occur before the reaction onset in ramped experiments. The findings indicate that in optimization of plastic cracking catalysts high external acidity and small particle size will play a significantly larger role compared to mesopore size.